The Role of PET/CT in the Evaluation of Skeletal Metastases - Kannivelu, Anbalagan; Loke, Kelvin S.H.; Kok, Tian Yue; Osmany, Saabry Yusof; Ali, Syed Zama; Suat-Jin, Lu; Ng, David Chee-Eng (Seminars in Musculoskeletal Radiology, 2014)
Osseous metastatic disease from malignancy is a common occurrence with significant patient morbidity and mortality as well as increasing health care expenditures. Patient management plans frequently change with the identification of skeletal metastasis and the upstaging of disease status. Bone scintigraphy remains the current mainstay of diagnostic imaging procedures in nuclear medicine for the early detection of skeletal metastasis owing to their high sensitivity. Emerging positron tracers and the increasing use and availability of hybrid single-photon emission computed tomography and positron emission tomography (PET)/computed tomography machines enable physicians to diagnose metastatic disease in bones with superior accuracy. This review introduces the basics of PET and the commonly used positron tracers used to evaluate skeletal metastases.
Keywords: skeletal metastases; [18F]-FDG PET; [18F]-NaF PET; Tc-99m diphosphonate bone scan; skeletal scintigraphy; hybrid imaging; image fusion